MATH SOLVE

2 months ago

Q:
# Choose the correct simplification of (4x3 + 3x2 − 6x) − (10x3 + 3x2).

Accepted Solution

A:

Answer:

-6x (x + 1)(x - 1)

Explanation:

Before we begin, remember the following:

(-ve) * (-ve) = +ve

(-ve) * (+ve) = -ve

(+ve) * (+ve) = +ve

(+ve) * (-ve) = -ve

a² - b² = (a + b)(a - b)

Now, for the given:

(4x³ + 3x² - 6x) - (10x³ + 3x²)

First, we eill remove the brackets based on the rules mentioned above. This will give us:

4x³ + 3x² - 6x - 10x³ - 3x²

Now, we will combine like terms as follows:

(4-10)x³ + (3-3)x² - 6x

-6x³ - 6x

Taking -6x as a common factor:

-6x (x² - 1)

Factoring the bracket as difference between two squares will give us the final simplest form:

-6x (x + 1)(x - 1)

Hope this helps :)

-6x (x + 1)(x - 1)

Explanation:

Before we begin, remember the following:

(-ve) * (-ve) = +ve

(-ve) * (+ve) = -ve

(+ve) * (+ve) = +ve

(+ve) * (-ve) = -ve

a² - b² = (a + b)(a - b)

Now, for the given:

(4x³ + 3x² - 6x) - (10x³ + 3x²)

First, we eill remove the brackets based on the rules mentioned above. This will give us:

4x³ + 3x² - 6x - 10x³ - 3x²

Now, we will combine like terms as follows:

(4-10)x³ + (3-3)x² - 6x

-6x³ - 6x

Taking -6x as a common factor:

-6x (x² - 1)

Factoring the bracket as difference between two squares will give us the final simplest form:

-6x (x + 1)(x - 1)

Hope this helps :)